What multiplies to -300 and adds to 13

Answers

Answer 1
Answer: 25 and -12 because when you subtract 12 from 25 you will get 13 and when you multiply 25 by -12 you will get -300
Answer 2
Answer: 25 and -12..........
Hope i helpd

Related Questions

Write an equation that requires at least three steps to solve and whose solution is x=3.5
Ordered pairs in which of these formats would always represent a function?A.(number of months since birth,age in years) B.(height,age) C.(age,weight) D.(age,grade in school)
Please can anyone solve 9n-10=4n+10
A teacher wants to compare the mean geology scores of two different classes. She is testing the null hypothesis that there is no difference in the population mean scores of the two classes. The difference of the sample means is 51.4. If the standard deviation of the distribution of the difference of sample means is 16.66, what is the 95% confidence interval for the population mean difference? A. between -33.2 and +33.2 B. between -49.9 and +49.9 C. between -102.8 and +102.8 D. between -154.2 and +154.2
Which sentence fully illustrates that polygon ABCD is congruent to polygon PQRS?

567 ÷ 12 with working out

Answers

Answer:

Step-by-step explanation:

567 ÷ 12

= 47.25

Answer:

47.25

Step-by-step explanation:

An object that starts at rest accelerates until it is moving at 247 km/h. If it takes 1.7 minutes for this change to occur what is the average acceleration in m/s? 20 PTS!

Answers

I figured out the answer Chaseashley24! The answer to your question is:

0.673 m/s²

Hope this helps!

What is 3 times pi? pi is in the picture like that’s the symbol.

Answers

Answer:

9.424777960769

Step-by-step explanation:

Let f(x) = 3x2 + x − 3 and g(x) = x2 − 5x + 1. Find f(x) − g(x).

Answers

Substitute the two functions according to a given condition of function:
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
= 3x
² + x - 3 - x² + 5x - 1
= 2x
² + 6x - 4  or  2(x² + 3x - 2)
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
f(x) - g(x) = 3x² + x - 3 - x² + 5x - 1
f(x) - g(x) = 3x² - x² + x + 5x - 3 - 1
f(x) - g(x) = 2x² + 6x - 4

Which angle forms a vertical pair with nsm a.osl b.smn c.snm d.osn

Answers

Answer:  Option 'a' is correct.

Step-by-step explanation:

Since we have given that  ∠NSM,

we need to find is vertical angles of ∠NSM,

1) ∠OSL is a vertical angle of ∠NSM as it has one common vertex and all other are collinear points.

2) ∠SMN can't be vertical angle as  vertical angles must be equal at common vertex but it does not do that it forms angle on M rather than on S.

3) ∠SNM can't be vertical angles as vertical angles must be equal at common vertex but it does not do that it forms angle on N rather than on S.

4) ∠OSN can't be vertical angle as vertical angles must have only one common vertex but in this case it has two common vertex i.e. S and N. so it will be linear pair.

Hence, Option 'a' is correct.

How do I complete each pattern, Example 1 block, 3 blocks,6 blocks

Answers

Well,

This could be an arithmetic sequence.
1 + 2 = 3
3 + 3 = 6
6 + 4 = 10
10 + 5 = 15
15 + 6 = 21
...

This could also be a geometric sequence.
1*3=3
3*2=6
6*1=6
6*0=0
0*-1=0
0*(anything)=0
...